Nasolabial cyst: case report - Pereira Filho,Valfrido Antonio (2002)
The nasolabial cyst is classified as a fissural cyst, found outside the bone, and on the region corresponding to the nasolabial furrow and alar nose. This cyst is frequently asymptomatic with the most usual sign being alar nose elevation. In spite of the low occurrence of nasolabial cysts, it is important to recognize the clinical characteristics of this lesion. The purpose of this paper is to review the literature and discuss the histomorphology and etiology of this condition, showing treatment by surgical excision.